2015
DOI: 10.1103/physrevd.91.065031
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Kaluza-Klein modes in the string-cigar braneworld

Abstract: In this work we analyze the properties of the gravitational Kaluza-Klein (KK) modes in two stringlike braneworlds, the thin Gherghetta-Shaposhnikov (GS) model and the thick string-cigar model. The stringcigar model is a smooth generalization of the GS model that undergoes a Ricci geometrical flow. We find a new massless mode in both models satisfying the respective Schrodinger equations. By means of a numerical analysis, we obtain the complete graviton spectrum and its respective eigenfunctions. The KK spectru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…It is obvious from equation (24) that for a phaseindependent perturbing force and under the adiabatic approximation, there is no secular evolution of the osculating semi-major axis due to phase-independent anisotropic wind mass-loss [see also Veras et al (2013)]. On the other hand, according to equation (25) a secular change will be induced to the eccentricity if F aniso,q = 0.…”
Section: Anisotropic Wind Mass-lossmentioning
confidence: 99%
“…It is obvious from equation (24) that for a phaseindependent perturbing force and under the adiabatic approximation, there is no secular evolution of the osculating semi-major axis due to phase-independent anisotropic wind mass-loss [see also Veras et al (2013)]. On the other hand, according to equation (25) a secular change will be induced to the eccentricity if F aniso,q = 0.…”
Section: Anisotropic Wind Mass-lossmentioning
confidence: 99%
“…What is the post-fission fate of the particles? Scheeres (2018) and Veras & Scheeres (2020) demonstrated that multiple generations of radiation-induced rotational breakup of a nearly-spherical rubble pile can occur until the rubble pile has been broken down into its monolithic components. In contrast here, for a triaxial rubble pile aroundZTF J0139+5245, the situation is more complex: rotational breakups can occur repeatedly until the child particles become spherical (when β = 1 in equation 4) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As a star leaves the main sequence, its luminosity increases sufficiently to spin up minor planets to the point of rotational fission through the YORP effect (Veras et al 2014a;Veras & Scheeres 2020). Although the extent and location of the break-up depends on the physical parameters of the asteroids in question, Veras et al (2014a) claimed that asteroids under about 10 km in radius within about 7 au of their parent star are easily destroyed.…”
Section: Introductionmentioning
confidence: 99%
“…( 40) and obtain the massive modes. Adopting the usual boundary condition ψ (0) = ψ (∞) = 0 [11,46], the first massive modes are shown in Fig. 5.…”
Section: A Kaluza-klein Modesmentioning
confidence: 99%